The Influence of Social Media on Purchasing Decision Through Electronic Word of Mouth As a Variable of Mediation: The Influence of Social Media on Purchasing Decision Through Electronic Word of Mouth As a Variable of Mediation - Sulistiyani Sulistiyani; Frans Sudirjo (Jurnal Mantik, 2020)
The research objective is to examine the effect of social media on purchasing decisions with electronic word of mouth (e-WOM) as mediation. The sample used in this study is 140 customers in Joglo Agung Resto and Gallery Semarang City. The sampling technique used a probability sampling method with an accidental sampling technique. The research approach with quantitative methods with path analysis, using analysis tools namely SEM (Structural Equation Model) with the help of Amos version 20.0. The findings obtained in this study are that social media has a positive and significant effect on e-WOM customers in Joglo Agung Resto and Gallery Semarang City. Social media has a positive and significant influence on customer purchasing decisions at Joglo Agung Resto and Gallery in Semarang. E-WOM has a positive and significant influence on customer purchasing decisions at Joglo Agung Resto and Gallery in Semarang. E-WOM mediates partially the effect of social media on customer purchasing decisions at Joglo Agung Resto and Gallery Semarang City.